Development of Antioxidant Packaging Material by Applying Corn-Zein to LLDPE Film in Combination with Phenolic Compounds - Park, Hye-Yeon; Kim, Sung-Jin; Kim, Ki Myong; You, Young-Sun; Kim, So Yeon; Han, Jaejoon (WILEY, 2012)
Functional active packaging materials were successfully developed by incorporating antioxidant agents into corn-zein-laminated linear low-density polyethylene (LLDPE) film. The minimum effective concentrations of the active compounds (for example, thymol, carvacrol, eugenol) were determined and these compounds were then laminated into LLDPE films to develop corn-zein-laminated films with antioxidant agents. The release rate of antioxidant agents in gas and liquid media were determined along with the mechanical and water barrier properties of the films containing these compounds. Tensile strength and percentage elongation at break were reduced in the corn-zein-laminated LLDPE films when compared to typical LLDPE film. Furthermore, the ability of the corn-zein-laminated films to repel moisture decreased by approximately 12.2%, but was improved by incorporating hydrophobic antioxidant compounds in the corn-zein layer. Examination of release kinetics in the gas and liquid phases verified that antioxidants were effectively released from the films and inhibited oxidation during testing. Finally, the films were used for fresh ground beef packaging, and effectively inhibited lipid oxidation and had a positive effect on the color stability of beef patties during storage. These results indicate that the developed antioxidant films are a novel active packaging material that can be effectively implemented by the food industry to improve the quality and safety of foods. Practical Application: Zein protein, a by-product of corn processing industry, was laminated into plastic films in combination with natural phenolic compounds to develop antioxidant packaging films. The films demonstrated their efficient release patterns of antioxidant compounds, which are suitable for packaging applications and food protection.
Keywords: ESSENTIAL OILS; BEEF; THYMOL; CARVACROL; OXIDATION; RELEASE; MEAT